2020
DOI: 10.1111/age.12970
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association study identifies variants associated with hair length in Brangus cattle

Abstract: Summary Thermal stress limits beef cattle production and a shorter hair coat is a key thermoregulative adaptation that allows cattle to lose heat more efficiently. The objective of this study was to identify genetic variants associated with the length of the undercoat and topcoat of cattle utilizing 1456 Brangus heifers genotyped with the Bovine GGP F250 array. Seven SNPs in the PCCA gene were significantly associated with undercoat length. PCCA belongs to the biotin transport and metabolism pathway. Biotin de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In addition, these breeds can be kept on poor-quality pastures compared to other commercial breeds. Some of the genes identified in the ROH islands have been used for selection in different commercial cattle breeds to rear animals with shorter coats, improving thermotolerance in humid tropical climates [ 47 ]. Currently, studies should be conducted with native breeds, since cattle species face challenges every day, such as those associated with global climate changes that affect animal production.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these breeds can be kept on poor-quality pastures compared to other commercial breeds. Some of the genes identified in the ROH islands have been used for selection in different commercial cattle breeds to rear animals with shorter coats, improving thermotolerance in humid tropical climates [ 47 ]. Currently, studies should be conducted with native breeds, since cattle species face challenges every day, such as those associated with global climate changes that affect animal production.…”
Section: Discussionmentioning
confidence: 99%
“…In cattle, the PCCA gene has been associated with undercoat length and, as a result, with many aspects of thermoregulation adaptation. The regulation of fur length by the PCC gene is determined by its function in biotin transport and metabolism (Davila et al, 2020). Several reports have indicated that PCCA and PCCB gene activity is regulated by different diets and that the PCC enzyme is critical for propionate metabolism -a major substrate for gluconeogenesis in ruminants (Graber et al, 2010).…”
Section: Roh Hotspots and Their Gene Contentmentioning
confidence: 99%
“…Animal heat tolerance is a quantitative trait (Gaughan et al 2010;Li et al 2011;Chang et al 2012), and recent advancements in molecular genetic methodologies have facilitated the identification of the correlation between genetic variation at specific loci and their associated traits. Among these adaptive responses, the coat characteristics play a pivotal role in influencing the heat tolerance of animals under high ambient temperature and humidity conditions (Sarlo Davila et al 2020).…”
Section: Introductionmentioning
confidence: 99%